HUBUNGAN KEBIASAAN SARAPAN DAN FREKUENSI MAKAN DENGAN PERTUMBUHAN ANAK USIA 36-59 BULAN DI KOTA PALEMBANG - Nandita Swastika; Amrina Rosyada (Jurnal Endurance, 2023)
WHO data for 2018 states that growth problems are not only malnutrition, but also stunting and overnutrition. The 2018 Riskesdas data for the prevalence of under five nutritional status is 30.8%, this prevalence has decreased when compared to the 2013 Riskesdas data and the Toddler Nutrition Status survey in 2019 showing that the prevalence of under five stunting in Indonesia reached 27.67%. Research conducted by the Food Bank of Indonesia (FOI) in 2020 shows that as many as 27% of toddlers in Indonesia skip breakfast. Methods: Quantitative research using a cross-sectional study design. The research sample was 148 mothers with children under five using cluster random sampling for univariate and bivariate data analysis. Result: The results of bivariate analysis using the chi-square test showed that breakfast habits were associated with the growth of the height/age indicator (p value 0.011), weight/height (p value 0.015) and eating frequency associated with the growth of the height/age indicator (p value 0.030 ). Conclusion: There is a relationship between eating frequency and growth (TB/A), breakfast habits and growth (TB/A and BB/TB) in children aged 36-59 months, there is no relationship between eating frequency and growth (BB/A, BB /TB, and BMI/A) and breakfast habits with growth (BB/U and BMI/A) in children aged 36-59 months in Palembang City. Keywords: Growth, Breakfast Habits, Meal Frequency, Nutritional Status, Toddlers.